2015
DOI: 10.1155/2015/919142
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Polymerization Type and Reinforcement Method on Flexural Strength of Acrylic Resin

Abstract: The aim of this study was to evaluate the flexural strength of acrylic resin bars by varying the types of resin polymerization and reinforcement methods. Fourteen groups (N = 10) were created by the interaction of factors in study: type of resin (self-cured (SC) or heat-cured (HC)) and reinforcement method (industrialized glass fiber (Ind), unidirectional glass fiber (Uni), short glass fiber (Short), unidirectional and short glass fiber (Uni-Short), thermoplastic resin fiber (Tpl), and steel wire (SW)). Reinfo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 32 publications
0
21
0
Order By: Relevance
“…In addition, the present study is inconsistent with that conducted by Minami et al (36), who found no improvement in the fracture strength during their study of the repairing of heat-polymerized acrylic by reinforced self-polymerized acrylic with glass fibers. However, Fonseca et al (15) reported that there was an improvement in the fracture strength by adding glass fibers, whether in heat-or self-polymerized acrylic. The disagreement between the results of the present study and those reported by Minami et al (36) could be attributed to the difference in the position of fibers in the center of models in the former study.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In addition, the present study is inconsistent with that conducted by Minami et al (36), who found no improvement in the fracture strength during their study of the repairing of heat-polymerized acrylic by reinforced self-polymerized acrylic with glass fibers. However, Fonseca et al (15) reported that there was an improvement in the fracture strength by adding glass fibers, whether in heat-or self-polymerized acrylic. The disagreement between the results of the present study and those reported by Minami et al (36) could be attributed to the difference in the position of fibers in the center of models in the former study.…”
Section: Discussionmentioning
confidence: 99%
“…However, each method has its disadvantages; for example, high-impact strength resin has poor flexural strength compared to conventional acrylic resins (14). On the other hand, metal and glass fibers exhibit different mechanical properties, high elasticity and lack of resilience (15). Fibers have been demonstrated to be more effective than metal glass, where their lower modulus of elasticity compared to metals provides more favorable stress distribution pattern (15).…”
Section: Morais Et Al (5) Reported Thatmentioning
confidence: 99%
See 2 more Smart Citations
“…However, in cases of implant installation to retain and/or give support for complete dentures [6], TAAR present precarious mechanical properties and can frequently fracture [1][2][3]5,[7][8][9][10]. This can occur as a result of occlusal disharmony, overloading, fatigue and impact caused by accidents [11][12]. Specially during the osseointegration phase of a protocol type prosthesis, which usually presents cantilever [13], provisional prosthesis made entirely of TAAR may be used over the implants [6].…”
Section: Introductionmentioning
confidence: 99%